HOW EASY IS IT GETTING INTO A CAR FOLLOWING TOTAL KNEE ARTHROPLASTY? (International Journal of Physiotherapy, 2020)
Background: Patients often enquire when they can start driving following total knee arthroplasty (TKA) surgery. Brake response time is an essential factor when resuming driving, and this has been extensively reported, but no data is available on when the patient can get safely in and out of a car based on the restricted knee flexion.Methods: We investigated the degree of difficulty and required knee flexion (RKF) to get into different car types, comprised of Sedans and Sports Utility Vehicles (SUV), using 11 volunteers with healthy knees. We used an electronic goniometer to record knee flexion required to get into the driver's seat, and participants were asked about their perceived difficulty getting into the car using a Visual Analog Scale (VAS) score (1 no difficulty to 10 impossible). We then restricted the knee flexion to 90, 60 and 30 degrees (using braces) to mimic knee stiffness following TKR surgery.Results: We observed that the mean range of knee flexion to get into a car comfortably was 101.8 degrees on the left and 110.6 degrees on the right. Restricting knee flexion to 60 and 30 degrees increased the leading leg entry time and led to abnormal body movements more so with SUV's compared to Sedans. This was confirmed by higher VAS scores for SUV's (p